In situ produced hydrogen peroxide by biosynthesized Palladium nanoparticles and natural clay mineral for Highly-efficient Carbamazepine degradation - Jiaxin Shi; Baogang Zhang; Wei Wang; Wei Zhang; Du, Penghui; Liu, Wen; Xing, Xuan; Dahu Ding; Guocheng Lv; Qing Lv; Lin Guo (Chemical Engineering Journal, 2021)
Fenton reaction is an effective method to remove refractory organics such as carbamazepine (CBZ) from water streams. Nevertheless, its application is greatly compromised by extra hydrogen peroxide (H2O2) addition and iron mud accumulation. Herein, Fenton-like process with in situ produced H2O2 by biosynthesized palladium nanoparticles (bioPd-NPs) and natural iron-bearing clay minerals is proposed for CBZ degradation. The bioPd-NPs prepared by Shewanella loihica PV-4 were in the size range of 5–20 nm, which catalyzed the in situ production of H2O2 from formic acid (FA) and oxygen. Then the in situ generated H2O2 underwent Fenton-like reactions with nontronite for CBZ degradation. With bioPd-NPs and nontronite dosage of 1 g/L and FA concentration of 20 mM, the complete CBZ (10 mg/L) degradation was achieved within 60 min. Oxidative radicals such as HO· and H2O2 generated in our constructed system played key roles in CBZ degradation. Intermediates/products identification and theoretical calculation revealed that hydroxylation was the main CBZ degradation pathway. This work provides a promising Fenton-like technology for elimination of CBZ from environment with prevention of additional H2O2 supplementation and excessive iron mud production.
Keywords: Biosynthesis; Carbamazepine; Fenton-like process; Natural clay minerals; Palladium nanoparticles